Distribution of innate efflux-mediated aminoglycoside resistance among different Achromobacter species. (March 2016) - Bador, J.; Neuwirth, C.; Liszczynski, P.; Mézier, M.-C.; Chrétiennot, M.; Grenot, E.; Chapuis, A.; de Curraize, C.; Amoureux, L.
Abstract: Achromobacter spp. are emerging respiratory pathogens in cystic fibrosis patients. Since 2013 the genus Achromobacter includes 15 species for which innate antibiotic resistance is unknown. Previously the AxyXY-OprZ efflux system has been described to confer aminoglycoside (AG) resistance in A. xylosoxidans. Nevertheless, some Achromobacter spp. strains are susceptible to AG. This study including 49 Achromobacter isolates reveals that AG resistance is correlated with different Achromobacter spp. It is noteworthy that the axyXY-oprZ operon is detected only in AG-resistant species, including the most frequently encountered in cystic fibrosis patients: A. xylosoxidans, A. ruhlandii, A. dolens and A. insuavis.